Recent Approaches in Understanding Evangelization in New Spain - Christensen, Mark Z. (History compass, 2016)
This article surveys scholarship on the evangelization of the natives of New Spain that challenge the myths and assumptions behind a "spiritual conquest." Aided by native-language sources and armed with a more critical reading of those Spanish, contemporary works debunk many myths associated with the spiritual conquest including those advocating a complete and finished conversion, the dominant role of the Spanish clergy, and a monolithic view of the Church, its institutions, and its implementation throughout New Spain. Recent scholars view conversion as a negotiated and fluid state that moved beyond syncretism and expose the major role native assistants played in evangelization. Furthermore, scholars increasingly illustrate the various versions of Catholicism, its apparatuses, and its participants as they continue to challenge a spiritual conquest.